Respon Hasil Cabai Rawit (Capsicum frutescens L.) pada Umur Pemangkasan Pucuk Dan Dosis TrichokomposRespon Hasil Cabai Rawit (Capsicum frutescens L.) pada Umur Pemangkasan Pucuk Dan Dosis Trichokompos - Putri, Mila Yunianysyah; Dewanti, F. Deru; Hidayat, Ramdan (BIOEDUSCIENCE, 2024)
Background: Increasing the productivity of Chili pepper plants can be done by pruning shoots and using trichotomous biofertilizer as an alternative to chemical fertilizers. This study aims to determine the effect of treating shoot pruning age and adding trichotomous doses on Chili pepper plant yields. Methods: This experiment used a Randomized Block Design with two factors. The first factor is the age of shoot pruning, which consists of 4 treatment levels, namely P0 = No pruning, P1 = shoot pruning 14 HST, P2 = shoot pruning 21 HST, P3 = shoot pruning 28 HST and trichotomous dose as the second factor consisting of 4 treatment levels, namely T0 = Without trichotomous, T1 = 600g/plant, T2 = 800 g/plant, and T3 = 1000 g/plant, so that 16 treatment combinations were obtained with three replications. Results: The results showed that the combination of pruning age treatment of 28 HST and trichotomous dose of 800g/plant produced the best number of flowers. A pruning age of 28 HST gave the best results on the number of leaves, leaf area, productive branches, total number of fruits per plant, and total fruit weight per plant. A trichotomous dose of 800 g/plant gave the best results on plant height, number of productive branches, total number of fruits per plant, and total fruit weight per plant. Conclusion: The pruning age of shoots and trichotomous doses affect the yield of Chili pepper plants.